Nonlinear Systems Root-Locus Design - Dervinienė, A.; Daunoras, J.; Januševičius, V. (Elektronika ir Elektrotechnika, 2006)
This article deals with a generalized method and procedures for analysis of nonlinear control systems using describing function with root – locus techniques. The presented analytical approach and procedures leads to determine pole – placement in complex s plane of the equivalent characteristic equation, stability and transient response characteristics of nonlinear system. The root – locus technique is available to nonlinear control systems analyst more direct and simpler than frequency – domain methods. Ill. 4, bibl. 3 (in Lithuanian; summaries in English, Russian and Lithuanian).